13‐3: Improvement of Blue Pixels in OLED Panels with more Efficient Fluorescent and TADF Emitters. Issue 1 (25th September 2020) - Baumann, Thomas; Budzynski, Matthias; Kasparek, Christian; Dueck, Sebastian; Ochsmann, Julian
Abstract : The missing high‐efficiency Blue OLEDs are still the bottleneck for the power consumption in today's OLED panels. One way to improve the efficiency of the blue pixel is the use of narrow‐type fluorescent emitters in a classical fluorescent stack for top‐emission OLED devices where the optical cavity effect favors narrow over a broader emission. In this paper, we will show how narrow‐type fluorescent emitters can deliver >30% efficiency improvement over traditional commercial fluorescent blue emitters to reach >200 cd/A/CIEy in top‐emission devices. For further efficiency increase, those fluorescent emitters can be combined with TADF emitters which can increase the internal quantum efficiency from 25% to 100%. In order to make such a hyper‐fluorescent system work efficiently, the combination of TADF and fluorescent emitter has to be chosen carefully as they have to match the materials perfectly.